Icings and their role as an important element of High Arctic glacier forefields - Sobota, Ireneusz (Bulletin of Geography. Physical Geography Series, 2016)
This study investigates the icings and their role as an important element of glacier forefields which are observed in the Kaffiøyra region in Svalbard. The emergence or disappearance of icings is one of the effects of changes observed in the area of a glacier and its catchment in the High Arctic. Icings have been examined with the observations carried out both in summer and from winter to spring in 1996-2015. The main objective was focused on the location and surface changes of the icings, as this is important for their responses to changes which occur across the cryosphere. In the forefields of most glaciers in the Kaffiøyra region, a generally falling trend is observed as regards the size of icing fields, with single periods when it increased. During the most recent five years, they were not so large as in the preceding years. The degradation of High Arctic icings mainly occurs in summer, generally as a result of surface and mechanical ablation. The reach of icings is rather variable and their surface and thickness tend to change year by year, depending on hydrological conditions in the glacier’s system. One of the effects of changes observed within a glacier and its catchment in the High Arctic is an emergence or disappearance of icings. Regardless of the causes of their formation, their size, range and reach are related to the intensity of melting during a given season, which is conditioned by the weather, and especially by the winter outflow from a glacier.